Elizabethan Period (The Golden Age of English Literature) - Ruly Adha (JADEs Journal of Academia in English Education, 2020)
English literature has been developed in some period. Each period has its own characteristics which portrayed the condition of the age. The period of English literature is started from Old English until Modern English. English literature becomes glorious when Queen Elizabeth I ruled England. This age is known as Elizabethan period. In this period, there are many literary works such as poetry, drama which are produced by famous artists. The literary works produced in Elizabethan period is famous and the existence of the literary works can be seen nowadays. Furthermore, some literary works, such as drama, are reproduced into movie. Therefore, this period is also known as the golden age of English Literature.